2014
DOI: 10.1089/end.2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Local Steroids for Urethra Strictures: A Systematic Review and Meta-Analysis

Abstract: The use of local steroids with IU seems to prolong time to stricture recurrence but does not seem to affect the high stricture recurrence rate following IU. When local steroids are applied with complementary intention, the disease control outcomes are encouraging. Further robust comparative effectiveness studies are now required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 20 publications
4
32
0
1
Order By: Relevance
“…A double-blind, placebo controlled randomized trial of anterior urethral strictures undergoing DVIU compared triamcinolone with sterile water, however while there was a delay in stricture recurrence of 4–5 months, there was no significant difference in overall rates of stricture recurrence (51), consistent with a meta-analysis of steroids as an adjunct to internal urethrotomy (52). Mazdak et al undertook two prospective randomized controlled trials to determine if internal urethrotomy for anterior urethral strictures with submucosal injection of triamcinolone (45) or MMC (47) was more effective than internal urethrotomy alone.…”
Section: Managementmentioning
confidence: 67%
“…A double-blind, placebo controlled randomized trial of anterior urethral strictures undergoing DVIU compared triamcinolone with sterile water, however while there was a delay in stricture recurrence of 4–5 months, there was no significant difference in overall rates of stricture recurrence (51), consistent with a meta-analysis of steroids as an adjunct to internal urethrotomy (52). Mazdak et al undertook two prospective randomized controlled trials to determine if internal urethrotomy for anterior urethral strictures with submucosal injection of triamcinolone (45) or MMC (47) was more effective than internal urethrotomy alone.…”
Section: Managementmentioning
confidence: 67%
“…[8] On that basis; Sciarra et al [9] used antiinflammatory drugs to reduce urethral strictures after TURP and suggested that COX-2 inhibitors can prevent development of post TURP urethral stricture. Yet, based on the same logic, several adjuvant therapies including colchicine [10] , mitomycin-c [11] , triamcinolone [12] , and corticosteroids [13] , which all have anti-inflammatory effects, have been used to treat urethral strictures either systematically or locally.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experimental and clinical studies have been performed to explore the efficacies of different molecules for preventing US formation. [20][21][22] Metalloproteinase-1 is another agent that has been used in an attempt to alleviate US after urethral injury. In one study, metalloproteinase-1 reportedly induced a lower collagen concentration in the traumatized region of the experimental group than the control group, and the researchers concluded that it contributed to the maintenance of urethral patency.…”
Section: Discussionmentioning
confidence: 99%